(untitled) (Scottish Historical and Archaeological Internet Reports, 2005)
The cairn at Olcote formed the latest recognisably prehistoric component of a site which perhaps developed since the Neolithic. The formless array of pits sealed beneath the cairn almost defies interpretation. Such confused post and pit patterns are common in Neolithic sites of probable domestic character, and it is conceivable that the pits preserved beneath the cairn at Olcote fall into this category. The cairn itself is of unusual morphology, dating from the mid 2nd millennium BC. Recent excavations in the Hebrides have revealed cairns of strikingly similar morphology and these are discussed here. Soil micromorphology has demonstrated that the topsoil was stripped prior to its construction and the body of the cairn was formed of ash from burnt peaty turves and peaty soil.